Reducing the dust generation of haul road by improving water holding capacity with the application of synthesised polyacrylamide at Laboratory Condition - Kashi V.K.; Karmakar N.C.; Krishnamoorthi S.; Sonker E.; Adhikary P.; Tiwari R. (My University, 2025)
Surface mining method enormously affects the environment in terms of fugitive dust emission than underground mining method. All the several sources of dust emission from opencast mining, haul road transportation system are the main source of fugitive dust. In this research article, a biodegradable polyacrylamide (PAM) was used to suppress dust generation from haul road of mine. It improves the moisture carrying capacity of haul road than the water. PAM has been synthesized by free radical polymerization process using ceric ammonium nitrate initiator. It was characterized by 1H NMR, IR & intrinsic viscosity measurements, whereas size distribution of haul road dust was measured by sieve analysis. Laboratory work has been carried out to investigate the water holding capacity of haul road dust particles using PAM solution and compared with only water for 8 hours duration. The temperature of the chamber was kept constant at 35°C while relative humidities (RH) varied from 40% to 70%. It was observed that moisture retention of dust with the application of PAM solution and only water were 25.65% and 20.4% at 70% RH and 7.14% and 1.65% at 40% RH, respectively after 8 hours. © 2020 Technoscience Publications. All rights reserved.